Monthly Variation in Flux of Inorganic Nutrients From Submarine Groundwater Discharge in a Volcanic Island: Significant Nitrogen Contamination in Groundwater - Kim, Jeonghyun; Song, Byung-Chan; Lee, Min-Young; Kim, Tae-Hoon (Frontiers in Marine Science, 2022)
To determine nutrient fluxes derived from submarine groundwater discharge (SGD), we conducted monthly hydrological surveys on the coast of Jeju, a volcanic island located in the southern sea of Korea. The concentrations of dissolved inorganic nitrogen (DIN), dissolved inorganic phosphorus (DIP), and dissolved silicon (DSi) were significantly correlated with salinity, indicating that fresh SGD (FSGD) is a major nutrient source in Jeju Island where no other coastal freshwater origins exist. Based on a DSi-mass balance model, seepage rate of FSGD was found to depend on 5-day precipitation before sampling campaigns, which immediately permeated via porous aquifers. Thus, the FSGD-driven nutrient fluxes were generally higher in rainy season (July–August) and September 2019 when typhoons occurred. However, high DIN and DIP fluxes were found during spring (March–May), even at low seepage rate, perhaps by a fertilizer input from agriculture activity. This study highlights that large variation of the SGD-driven nutrient fluxes was caused by environmental and anthropogenic factors and emphasizes on the importance of long-term investigation.